TEACHING EFFECTIVENESS: IMPACT OF PERSONALITY TEACHING STRATEGIES OF TEACHERS TEACHING EFFECTIVENESS: IMPACT OF PERSONALITY TEACHING STRATEGIES OF TEACHERS - Suman,; Tiwari, Dr. Shruti (IJRDO - Journal of Social Science and Humanities Research, 2018)
Effective teaching create a difference between effective and non-effective teachers. Effective teaching is more beneficial to achieving goals of education/curriculum and provide learning opportunities within sufficient manner, and also keep command/mastery on the subject and believe in originality in teaching. Actually students like to those teachers who teach in effective way and use interesting methods. Many factors that affect the teaching effectively such as teachers’ behaviour, assessment way, teacher knowledge, classroom activities, effective feedback, teaching strategy and teaching experience etc. How teaching strategies and teacher personality aspects so helpful to create classroom so effective where students learn in easiest way and can generate interest for study among students Even then parents as well as students give entire focus on coaching for career instead of school. So this question raised why students give priorities to coaching’s teachers, which methods and teaching strategies they adopt in classroom to teach to students which created gap in student perceptive for teachers.